32.3: Enhancing Interferometric Display Color View Angle Performance Using a Fiber Array Film. Issue 1 (June 2015) - Ma, Jian; Hong, Brandon; Hong, John; Chang, Tallis
Abstract : Viewing angle dependent color shift is a fundamental property of all interferometric displays, including Qualcomm's Mirasol™ displays. We present a solution to reduce the color shift using a fiber array fabricated in a polycarbonate film via nano embossing. We discuss FDTD simulation, fabrication, and experimental result.